Kolizja kwalifikacji. Przedawnienie roszczeń. Stan aktualny - uwagi de lege ferenda: [Collision of qualifications. Statute of limitations of claims. The current state of affairs - de lege ferenda comments] (Studia Prawnicze / The Legal Studies, 2002)
Autorka przybliża czytelnikom pojęcie kwalifikacji i związanym z nim zagadnieniem kolizji kwalifikacji. Przedstawia dwa nurty pojmowania i stosowania prawa w doktrynie prawa prywatnego międzynarodowego mianowicie pierwszy, w który wiąże się z przyjęciem stosowania lex fori jako prawa rządzącego wszystkimi stosunkami prawnymi na terytorium państwa oraz drugi, w którym jest dopuszczalne stosowania prawa innego niż lex fori. Ponadto autorka przedstawia regulacje prawne dotyczące przedawnienia roszczeń. The author introduces readers to the concept of qualification and the related issue of qualification conflict. She presents two trends in the understanding and application of law in the doctrine of private international law, namely the first trend, which involves the acceptance of the application of the lex fori as the law governing all legal relations within the territory of the state, and the second trend, according to which a law other than the lex fori can be applied. The author also presents legal regulations related to the statute of limitations for claims.